Comprehensive assessment of CO2 methanation: which H2 production pathway is practicable for green methane production in terms of technical, economic, and environmental aspects?. Issue 23 (11th November 2021) - Choe, Changgwon; Lee, Boreum; Kim, Ayeon; Cheon, Seunghyun; Lim, Hankwon
Abstract : The analytic hierarchy process was performed to determine the best alternative for green methane production based on the results of technical assessment, economic analysis, and life cycle assessment. Abstract : In this work, a comprehensive study of CO2 methanation by coupling process simulation, economic analysis, and life cycle assessment (LCA) was conducted to find out the most practicable pathway for green methane production in terms of technical, economic, and environmental aspects. For this work, different renewable energy resources, such as hydropower, wind power, and solar power, and water electrolysis, like alkaline water electrolysis (AWE) and proton-exchange membrane water electrolysis (PWE), leading to 6 scenarios for H2 production were considered. From the economic analysis in terms of itemized cost estimation, the levelized cost of methane (LCOM) for scenarios 1 to 6 was obtained as 0.108, 0.118, 0.144, 0.121, 0.132, and 0.159 kWh −1, respectively. In addition, from LCA, the respective quantified environmental impacts ( i.e., CO2 emission) were obtained as 0.347, 0.813, 2.33, 0.537, 0.842, and 2.52 kg CO2 -eq kg H2 −1 for scenarios 1 to 6, respectively. And then, the analytic hierarchy process (AHP) was carried out to decide on the most appropriate renewable energy and water electrolysis based on different criteria of renewable energy capacity with Technology readiness level (TRL) of water electrolysis, LCOM, and CO2 emission for technical, economic, and environmental criteria, respectively. From this work, H2 production from AWE with wind power ( i.e., scenario 2) was selected to be the best pathway for green methane production owing to the narrow priority range of 0.130–0.191. Furthermore, scenario 5 ( i.e., PWE with wind power) was determined to be the second pathway with the same reason.